2016
DOI: 10.1177/2151458515625296
|View full text |Cite
|
Sign up to set email alerts
|

Orthogeriatric Service Reduces Mortality in Patients With Hip Fracture

Abstract: Introduction:Orthogeriatric service has been shown to improve outcomes in patients with hip fracture. The purpose of this study is to evaluate the effect of orthogeriatrics at Bispebjerg University Hospital, Denmark. The primary outcome is mortality inhospital and after 1, 3, and 12 months for patients with hip fracture. The secondary outcome is mortality for home dwellers and nursing home inhabitants.Materials and Methods:This is a retrospective clinical cohort study with an historic control group including a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 24 publications
2
31
0
Order By: Relevance
“…In order to improve outcomes following hip fracture surgery, it is imperative to identify modifiable factors that could possibly aid survival and function [ 23 ]. There have been promising results where an improved and close cooperation between orthopaedic surgeons and geriatricians have led to a reduction in mortality [ 24 ] aided by systematic and sustained quality improvement efforts [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to improve outcomes following hip fracture surgery, it is imperative to identify modifiable factors that could possibly aid survival and function [ 23 ]. There have been promising results where an improved and close cooperation between orthopaedic surgeons and geriatricians have led to a reduction in mortality [ 24 ] aided by systematic and sustained quality improvement efforts [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…19 There is an urgent need for randomised controlled trials of treatment options and disease management in this frail group of patients. The use of CINPWT was a non-inferior treatment compared with stump bandage.…”
Section: Discussionmentioning
confidence: 99%
“…Major amputated patients have higher mortality rates at all points of time postoperatively than, for instance, hip fracture patients. 19 There is an urgent need for randomised controlled trials of treatment options and disease management in this frail group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…19 Even with integrated orthogeriatric care for hip fracture patients, the mortality rate remains high. Stenqvist et al reported that integrated orthogeriatric care decreased the inhospital mortality rate from 6.3% to 3.1%, 20 while Forni et al found that it reduced the 30-day mortality rate from 4.3% to 3.4%. 21 Furthermore, Folbert et al concluded that integrated orthogeriatric care lowered the 12-month mortality rate from 35.1% to 23.2%.…”
Section: Discussionmentioning
confidence: 99%